A metal oxide loaded flower-like SnO2-based composite catalyst, a preparation method and application thereof

CN122702447BActive Publication Date: 2026-10-27SHANDONG HAIHUA CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202611207797.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-11
Publication Date
2026-10-27
Estimated Expiration
2046-08-11

AI Technical Summary

Technical Problem

但是,现有技术中报道的SnO2催化材料多为简单颗粒状或致密结构,其表面活性位点暴露程度有限(如中国专利CN108726558A、CN106757527A、CN114804190A),导致采用其作为金属氧化物载体使用时,对负载组分的固定能力和界面协同作用仍然不足,难以有效抑制金属氧化物的团聚和失活行为

Benefits of technology

(1)本发明的负载金属氧化物的花状SnO2基复合催化剂的制备方法,通过构建由多级纳米片自组装形成的花状SnO2微米载体,使载体具有层级结构特征、较多表面暴露位点以及较高的结构缺陷密度,从而有利于提供更多活性组分负载位点,并改善载体与活性组分之间的接触状态。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122702447B_ABST
    Figure CN122702447B_ABST
Patent Text Reader

Abstract

The application provides a flower-shaped SnO2-based composite catalyst loaded with metal oxides and a preparation method and application thereof, and relates to the field of cyclohexane catalysis technology.The preparation method comprises the following steps: adding a sodium hydroxide solution into an ethanol aqueous solution, then uniformly mixing the sodium hydroxide solution with tin tetrachloride pentahydrate and citric acid, and obtaining a flower-shaped SnO2 micron carrier through a hydrothermal reaction and annealing treatment; and the flower-shaped SnO2 micron carrier is impregnated in a transition metal nitrate solution, then dried and calcined to obtain the flower-shaped SnO2-based composite catalyst loaded with metal oxides.The composite catalyst can avoid the problems of migration and agglomeration of metal oxides on the surface of the carrier under high-temperature or long-time reaction conditions, and has good catalytic activity, target product selectivity and long-term cyclic stability in the preparation of cyclohexanol and cyclohexanone through catalytic oxidation of cyclohexane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of cyclohexane catalysis technology, and in particular to a flower-like SnO2-based composite catalyst supported on metal oxides, its preparation method, and its application. Background Technology

[0002] Catalytic oxidation of alkanes is a crucial reaction in the fields of fine chemicals and new chemical materials. The selective oxidation of alkanes, exemplified by cyclohexane, is widely used in the preparation of important chemical intermediates such as cyclohexanol and cyclohexanone, playing a vital role in the production of nylon, engineering plastics, and related high-value-added chemicals. However, the high C–H bond energy and stable molecular structure of alkanes make them difficult to activate effectively under mild conditions. Furthermore, the oxidation of cyclohexane is often accompanied by free radical chain reactions, which can easily lead to over-oxidation or even deep combustion, posing significant challenges to the selectivity of the target product and the controllability of the reaction process. Therefore, this reaction places high demands on the activity, selectivity, and long-term operational stability of its catalysts.

[0003] Currently, metal oxide catalysts are widely studied and applied in alkane oxidation reaction systems due to their relatively low preparation cost, good environmental friendliness, and strong tunability of composition and structure. However, single metal oxide catalysts typically suffer from problems such as a limited number of active sites, insufficient ability to control surface reactive species, and susceptibility to sintering, agglomeration, or structural reconstruction during the reaction process. These issues make it difficult to simultaneously achieve high reactivity and good stability under actual reaction conditions, thus limiting their industrial application prospects.

[0004] To address these issues, existing technologies typically involve loading metal oxides onto the surface of inorganic supports to improve their dispersibility and utilization efficiency. Commonly used support materials include inorganic oxides such as alumina, silica, and titanium dioxide (e.g., Polyhedron 2019, 157:90–106). However, in practical applications, these supports are mostly chemically inert surfaces, resulting in weak interfacial interactions with metal oxides and making it difficult to form stable and efficient synergistic catalytic interface structures. During the reaction, metal oxides still tend to migrate and aggregate on the support surface, especially at higher temperatures or under prolonged reaction conditions, further reducing their dispersion and the stability of active sites, thus limiting the continuous improvement of catalytic performance.

[0005] SnO2, as an important semiconductor metal oxide material, possesses excellent thermal and chemical stability and has been gradually introduced into the field of catalysis in recent years (e.g., Chinese patents CN120866864A and CN119701951A). Existing research shows that by controlling the morphology and structure of SnO2, its specific surface area and surface reactivity can be improved to some extent. However, most SnO2 catalytic materials reported in the prior art are simple particulate or dense structures with limited exposure of surface active sites (e.g., Chinese patents CN108726558A, CN106757527A, and CN114804190A). This results in insufficient fixation capacity for the supported components and interfacial synergy when used as a metal oxide support, making it difficult to effectively inhibit the aggregation and deactivation of metal oxides.

[0006] Therefore, there is an urgent need to develop a support material that is structurally stable, has strong interfacial interactions, can effectively immobilize metal oxides, and is suitable for loading through a simple process. Based on this, a composite catalyst system with high activity, high selectivity, and good cycle stability should be constructed to meet the actual needs of catalytic materials for the selective oxidation of alkanes such as cyclohexane. Summary of the Invention

[0007] To address the technical problems existing in the prior art, this invention provides a method for preparing a flower-like SnO2-based composite catalyst supported on metal oxides. By constructing a specific flower-like SnO2 micron support, the support possesses both hierarchical morphology advantages and a large specific surface area advantage. Furthermore, transition metal oxides are loaded onto the surface of the flower-like SnO2 micron support to construct a composite catalyst system with strong interfacial interactions, thereby achieving stable dispersion of active components, synergistic enhancement of interfacial interactions, and improved catalytic performance. This effectively avoids the migration and aggregation of metal oxides on the support surface under high-temperature or long-term reaction conditions, and effectively improves the stability of active sites.

[0008] The present invention also provides a flower-like SnO2-based composite catalyst supported on metal oxides prepared by the aforementioned method.

[0009] The present invention also provides the application of the flower-like SnO2-based composite catalyst supported on metal oxide in the catalytic oxidation reaction of cyclohexane. The flower-like SnO2-based composite catalyst supported on metal oxide can catalyze the preparation of cyclohexane alcohol and cyclohexanone from cyclohexane with high selectivity, and exhibits good catalytic activity, target product selectivity and long-term cycle stability during the reaction.

[0010] To solve the above technical problems, the technical solution adopted by the present invention is as follows: A method for preparing a flower-like SnO2-based composite catalyst supported on a metal oxide comprises the following steps: Step S01: Add sodium hydroxide solution to ethanol aqueous solution, disperse and dissolve, then add tin tetrachloride pentahydrate and citric acid, mix well to obtain precursor solution; after hydrothermal reaction of precursor solution in closed environment, collect solids by centrifugation, wash and dry solids, and then anneal to obtain flower-shaped SnO2 micron support. Step S02: Add the flower-shaped SnO2 micron support to a transition metal nitrate solution for impregnation treatment; after the impregnation treatment is completed, centrifuge to collect the solid, and then calcine the solid after drying to obtain the flower-shaped SnO2-based composite catalyst loaded with metal oxide.

[0011] Preferably, in step S01, the concentration of the sodium hydroxide solution is 0.8-1.2 mol / L; The volume concentration of ethanol in an aqueous ethanol solution is 40-60%.

[0012] Preferably, in step S01, the concentration of sodium hydroxide in the precursor solution is 0.3-0.5 mol / L; The molar ratio of sodium hydroxide, tin tetrachloride pentahydrate, and citric acid in the precursor solution is 9-12:1:0.2-0.5.

[0013] Preferably, in step S01, the temperature of the hydrothermal reaction is 150-250℃, and the time of the hydrothermal reaction is 15-30h.

[0014] Preferably, in step S01, the annealing process is carried out in an air atmosphere, the annealing temperature is 400-550℃, and the annealing time is 3-7 hours.

[0015] Preferably, in step S02, the transition metal nitrate used in the transition metal nitrate solution is at least one of the following: cobalt nitrate, copper nitrate, ferric nitrate, manganese nitrate, and zinc nitrate; The total molar concentration of transition metal nitrates in a transition metal nitrate solution is 0.1-1.5 mol / L.

[0016] Preferably, in step S02, the mass-to-volume ratio of the flower-like SnO2 micron support to the transition metal nitrate solution is 0.9-1.2 g: 100 mL.

[0017] Preferably, in step S02, the immersion treatment temperature is room temperature, and the immersion treatment time is 5-18 hours; The calcination process is carried out in an air atmosphere at a temperature of 400-500℃ for 3-6 hours.

[0018] A flower-like SnO2-based composite catalyst supported on metal oxides was prepared using the aforementioned method.

[0019] Application of the aforementioned flower-shaped SnO2-based composite catalyst supported on metal oxide in the catalytic oxidation of cyclohexane to prepare cyclohexanol and cyclohexanone.

[0020] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) The method for preparing the flower-like SnO2-based composite catalyst supported on metal oxides of the present invention constructs a flower-like SnO2 micron support formed by the self-assembly of multi-level nanosheets, so that the support has hierarchical structure characteristics, more surface exposed sites and higher structural defect density, which is conducive to providing more active component loading sites and improving the contact state between the support and the active component.

[0021] (2) In the preparation method of the flower-shaped SnO2-based composite catalyst supported on metal oxides of the present invention, the flower-shaped SnO2 micron support can maintain a relatively stable hierarchical structure and provide more surface exposure sites after annealing treatment, which is beneficial to improve the dispersibility and fixation stability of transition metal oxides on the support surface and inhibit the migration and aggregation of active components during the reaction process.

[0022] (3) In the preparation method of the flower-shaped SnO2-based composite catalyst supported on metal oxides of the present invention, a synergistic catalytic interface with strong interfacial interaction is constructed by combining the transition metal oxide with the flower-shaped SnO2 micron support. On the one hand, it is beneficial to the contact between the reactants and the active sites, and on the other hand, it is beneficial to improve the catalytic activity and target product selectivity of the catalyst in the cyclohexane oxidation reaction.

[0023] (4) The flower-like SnO2 support-transition metal oxide composite catalytic system constructed in this invention has both structural stability and interfacial stability, and can maintain a good dispersion state of active components during the cyclohexane catalytic reaction, thus which is beneficial to improving the stability of the catalyst for recycling.

[0024] (5) The flower-shaped SnO2-based composite catalyst supported on metal oxides of the present invention can be effectively used for the catalytic oxidation of cyclohexane to prepare cyclohexanol and cyclohexanone. It has good catalytic activity, target product selectivity and long-term cycle stability, and has good application prospects in the field of selective oxidation of alkanes.

[0025] (6) The preparation method of the flower-shaped SnO2-based composite catalyst supported on metal oxide of the present invention is easy to obtain raw materials, simple in preparation process, easy to control in preparation process, and conducive to industrial-scale production and application. Attached Figure Description

[0026] Figure 1 This is the SEM image of the flower-like SnO2 micron-sized carrier prepared in Example 1.

[0027] Figure 2 This is the SEM image of the flower-like SnO2-based composite catalyst supported on metal oxides prepared in Example 1.

[0028] Figure 3 This is the SEM image of the non-florescent SnO2-based composite catalyst supported on metal oxides prepared in Comparative Example 1.

[0029] Figure 4 The image shows the BET spectrum of the non-florescent SnO2 micron-sized support prepared in Comparative Example 1.

[0030] Figure 5 This is the BET spectrum of the flower-like SnO2 micron-sized carrier prepared in Example 1.

[0031] Figure 6 The image shows the XRD pattern of the flower-like SnO2 micron-sized carrier prepared in Example 1. Detailed Implementation

[0032] To provide a clearer understanding of the technical features, objectives, and effects of this invention, specific embodiments are now described. It should be noted that the following detailed descriptions are exemplary and intended to provide further explanation of the invention. Unless otherwise specified, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.

[0033] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the exemplary embodiments of the present invention. As used herein, "first," "second," etc., are used to distinguish similar objects and are not used to describe a particular order or sequence. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.

[0034] In a first aspect, embodiments of the present invention provide a method for preparing a flower-like SnO2-based composite catalyst supported on a metal oxide, comprising the following steps: Step S01: Add sodium hydroxide solution to ethanol aqueous solution, stir to dissolve, then add tin tetrachloride pentahydrate and citric acid, and continue stirring until completely dissolved to obtain precursor solution; after hydrothermal reaction of precursor solution in closed environment, collect solid matter by centrifugation, wash and dry solid matter, and then anneal to obtain flower-shaped SnO2 micron support. Step S02: Add the flower-shaped SnO2 micron support to the transition metal nitrate solution and perform impregnation treatment under stirring conditions to allow the transition metal precursor to be adsorbed and dispersed on the surface of the flower-shaped SnO2 micron support; after the impregnation treatment is completed, centrifuge to collect the solid, and then calcine the solid after drying to obtain the flower-shaped SnO2-based composite catalyst loaded with metal oxide.

[0035] The inventors discovered that, under alkaline conditions, the flower-like SnO2 micron-support, after hydrolysis and condensation of the tin source precursor and regulation of the crystal growth process by organic ligands, can preferentially form two-dimensional nanosheet structural units. These nanosheet structural units further undergo directional aggregation and self-assembly during the heating reaction, ultimately forming a flower-like hierarchical micron structure. This flower-like hierarchical structure is composed of a large number of staggered stacked nanosheets, with many exposed edge sites and pore channels, which is beneficial for the subsequent loading, dispersion, and interfacial contact of active components.

[0036] Furthermore, the inventors discovered that during the annealing and crystallization process, the flower-like SnO2 micron-sized support exhibits a relatively unsaturated surface atomic coordination and numerous exposed edge sites, resulting in a large number of surface defect sites. These surface defect sites are beneficial for improving the binding capacity and dispersion stability of the active components on the support surface, and may enhance the interfacial interaction between the support and the active components.

[0037] Preferably, in step S01, the concentration of the sodium hydroxide solution is 0.8-1.2 mol / L; and the volume concentration of ethanol in the ethanol aqueous solution is 40-60%.

[0038] Preferably, in step S01, the concentration of sodium hydroxide in the precursor solution is 0.3-0.5 mol / L; the molar ratio of sodium hydroxide, tin tetrachloride pentahydrate, and citric acid in the precursor solution is 9-12:1:0.2-0.5.

[0039] Preferably, in step S01, the temperature of the hydrothermal reaction is 150-250℃, and the time of the hydrothermal reaction is 15-30h.

[0040] Preferably, in step S01, the annealing process is carried out in an air atmosphere, the annealing temperature is 400-550℃, and the annealing time is 3-7 hours.

[0041] Preferably, in step S02, the transition metal nitrate used in the transition metal nitrate solution is at least one of the following: cobalt nitrate, copper nitrate, ferric nitrate, manganese nitrate, and zinc nitrate; more preferably, it is one of the following: cobalt nitrate, copper nitrate, and manganese nitrate. The total molar concentration of the transition metal nitrate in the transition metal nitrate solution is 0.1-1.5 mol / L.

[0042] Preferably, in step S02, the mass-to-volume ratio of the flower-like SnO2 micron support to the transition metal nitrate solution is 0.9-1.2 g: 100 mL.

[0043] Preferably, in step S02, the immersion treatment temperature is room temperature, and the immersion treatment time is 5-18 hours.

[0044] Preferably, in step S02, the calcination treatment is carried out in an air atmosphere, the calcination temperature is 400-500℃, and the calcination time is 3-6 hours.

[0045] Secondly, embodiments of the present invention also provide a flower-like SnO2-based composite catalyst supported on metal oxides prepared by the above preparation method.

[0046] Thirdly, the present invention also provides the application of the above-mentioned flower-shaped SnO2-based composite catalyst supported on metal oxide in the catalytic oxidation reaction of cyclohexane to prepare cyclohexanol and cyclohexanone.

[0047] Without being limited by theory, the inventors also discovered that the flower-like hierarchical structure prepared by the present invention can provide more accessible surface sites and mass transfer channels, and the surface structure features formed by annealing are further conducive to inhibiting the migration and aggregation of active components during the reaction process, thereby effectively improving the catalytic activity, target product selectivity and recycling stability of the composite catalyst for the catalytic oxidation of cyclohexane.

[0048] To enable those skilled in the art to better understand the technical solution of the present invention, the present invention will be further described below in conjunction with some specific embodiments.

[0049] Example 1 This embodiment provides a method for preparing a flower-like SnO2-based composite catalyst supported on a metal oxide, comprising the following steps: (1) Measure 50 mL of deionized water and 50 mL of anhydrous ethanol, mix them, place them in a beaker, and stir magnetically at room temperature to form a homogeneous mixed solution to obtain an ethanol aqueous solution; add 60 mL of sodium hydroxide solution with a concentration of 0.8 mol / L to the ethanol aqueous solution and continue stirring until it is completely mixed; after the sodium hydroxide solution is added, continue to add SnCl4·5H2O and citric acid, and continue stirring for 30 min until completely dissolved to obtain a precursor solution; the concentration of sodium hydroxide in the precursor solution is about 0.30 mol / L, and the molar ratio of sodium hydroxide, SnCl4·5H2O and citric acid is 10:1:0.3.

[0050] The precursor solution was transferred to a closed reaction vessel and subjected to a hydrothermal reaction at 200°C for 20 hours. After the hydrothermal reaction was completed, the solution was naturally cooled to room temperature, and the resulting solid was separated by centrifugation. The solid was washed three times with deionized water and anhydrous ethanol to remove residual reactants and byproducts. The washed solid was then vacuum dried at 60°C for 12 hours and placed in air for annealing at 450°C for 4 hours to obtain a flower-like SnO2 micronized carrier.

[0051] (2) Take 1.0 g of flower-shaped SnO2 micron support and add it to 100 mL of cobalt nitrate solution (cobalt nitrate concentration 0.5 mol / L). Impregnate the solid for 8 h at room temperature by magnetic stirring. After impregnation, separate and collect the solid by centrifugation. Dry the solid at 80 °C for 12 h. Place the dried solid in an air atmosphere and calcine at 450 °C for 4 h. After calcine, cool to room temperature to obtain the flower-shaped SnO2-based composite catalyst loaded with metal oxide, denoted as 1-CoOx / SnO2. The metal element content and metal oxide loading in the obtained composite catalyst are shown in Table 1.

[0052] This embodiment also provides a flower-like SnO2-based composite catalyst supported on metal oxides prepared by the aforementioned method.

[0053] Example 2 This embodiment provides a method for preparing a flower-like SnO2-based composite catalyst supported on metal oxides, using the technical solution of Example 1, but differing from Example 1 in that: In step (1), the molar ratio of sodium hydroxide, SnCl4·5H2O and citric acid in the precursor solution is adjusted to 9:1:0.2; the temperature of the hydrothermal reaction is adjusted to 150℃ and the time of the hydrothermal reaction is adjusted to 30h; the temperature of the annealing treatment is adjusted to 400℃ and the time of the annealing treatment is adjusted to 7h.

[0054] In step (2), the concentration of cobalt nitrate solution is adjusted to 0.1 mol / L; the impregnation time is adjusted to 18 h; the calcination temperature is adjusted to 400 °C; and the calcination time is adjusted to 6 h.

[0055] The remaining conditions were the same as in Example 1, and a flower-like SnO2-based composite catalyst loaded with metal oxides was prepared, denoted as 2-CoOx / SnO2. The metal element content and the equivalent loading of metal oxides in the obtained composite catalyst are shown in Table 1.

[0056] This embodiment also provides a flower-like SnO2-based composite catalyst supported on metal oxides prepared by the aforementioned method.

[0057] Example 3 This embodiment provides a method for preparing a flower-like SnO2-based composite catalyst supported on metal oxides, using the technical solution of Example 1, but differing from Example 1 in that: In step (1), the molar ratio of sodium hydroxide, SnCl4·5H2O and citric acid in the precursor solution is adjusted to 12:1:0.5; the temperature of the hydrothermal reaction is adjusted to 250℃ and the time of the hydrothermal reaction is adjusted to 15h; the temperature of the annealing treatment is adjusted to 550℃ and the time of the annealing treatment is adjusted to 3h.

[0058] In step (2), the concentration of cobalt nitrate solution is adjusted to 1.5 mol / L; the impregnation time is adjusted to 5 h; the calcination temperature is adjusted to 500 ℃; and the calcination time is adjusted to 3 h.

[0059] The remaining conditions were the same as in Example 1, and a flower-like SnO2-based composite catalyst loaded with metal oxides was prepared, denoted as 3-CoOx / SnO2. The metal element content and the equivalent loading of metal oxides in the obtained composite catalyst are shown in Table 1.

[0060] This embodiment also provides a flower-like SnO2-based composite catalyst supported on metal oxides prepared by the aforementioned method.

[0061] Example 4 This embodiment provides a method for preparing a flower-like SnO2-based composite catalyst supported on metal oxides, using the technical solution of Example 1, but differing from Example 1 in that: In step (2), the cobalt nitrate solution is replaced with an equal volume of copper nitrate solution with a concentration of 0.5 mol / L.

[0062] The remaining conditions were the same as in Example 1, and a flower-like SnO2-based composite catalyst loaded with metal oxides was prepared, denoted as 4-CuOx / SnO2. The metal element content and the equivalent loading of metal oxides in the obtained composite catalyst are shown in Table 1.

[0063] This embodiment also provides a flower-like SnO2-based composite catalyst supported on metal oxides prepared by the aforementioned method.

[0064] Example 5 This embodiment provides a method for preparing a flower-like SnO2-based composite catalyst supported on metal oxides, using the technical solution of Example 1, but differing from Example 1 in that: In step (2), the cobalt nitrate solution is replaced with an equal volume of manganese nitrate solution with a concentration of 0.5 mol / L.

[0065] The remaining conditions were the same as in Example 1, and a flower-like SnO2-based composite catalyst loaded with metal oxides was prepared, denoted as 5-MnOx / SnO2. The metal element content and the equivalent loading of metal oxides in the obtained composite catalyst are shown in Table 1.

[0066] This embodiment also provides a flower-like SnO2-based composite catalyst supported on metal oxides prepared by the aforementioned method.

[0067] Example 6 This embodiment provides a method for preparing a flower-like SnO2-based composite catalyst supported on metal oxides, using the technical solution of Example 1, but differing from Example 1 in that: In step (1), the concentration of sodium hydroxide solution added to the ethanol aqueous solution is adjusted to 1.2 mol / L, and the concentration of sodium hydroxide in the obtained precursor solution is about 0.45 mol / L; at the same time, according to the amount of sodium hydroxide added in the precursor solution, SnCl4·5H2O and citric acid are added to make the molar ratio of sodium hydroxide, SnCl4·5H2O and citric acid in the precursor solution 10:1:0.3.

[0068] The remaining conditions were the same as in Example 1, and a flower-like SnO2-based composite catalyst loaded with metal oxides was prepared, denoted as 6-CoOx / SnO2. The metal element content and the equivalent loading of metal oxides in the obtained composite catalyst are shown in Table 1.

[0069] This embodiment also provides a flower-like SnO2-based composite catalyst supported on metal oxides prepared by the aforementioned method.

[0070] To further clarify the actual loading of metal oxides in the flower-like SnO2-based composite catalysts with supported metal oxides prepared in Examples 1-6, each composite catalyst sample was subjected to acid digestion, and the contents of Co, Cu, or Mn elements were determined by ICP-OES. Since ICP-OES directly measures the mass fraction of metal elements, not the mass fraction of metal oxides, the measured metal element contents were converted to the corresponding metal oxide loadings in the form of Co3O4, CuO, or Mn3O4, respectively. The specific results are shown in Table 1. Table 1 Summary of metal oxide loading of composite catalysts in Examples 1-6

[0071] As shown in the table above, the cobalt oxide loading of the CoOx / SnO2 composite catalysts obtained in Examples 1-3 and Example 6 varies to some extent. This difference is not only related to the concentration of cobalt nitrate solution and impregnation time, but also to the preparation conditions of the flower-like SnO2 micron support. Different molar ratios of sodium hydroxide, SnCl4·5H2O, and citric acid, hydrothermal reaction temperature, hydrothermal reaction time, and annealing conditions will affect the morphology, specific surface area, surface defect sites, and number of precursor adsorption sites of the SnO2 support, thereby affecting the adsorption and fixation effect of transition metal precursors on the support surface. Therefore, the metal oxide loading in Examples 1-3 and Example 6 is not solely determined by the concentration of cobalt nitrate solution.

[0072] Examples 1, 4, and 5 used the same flower-shaped SnO2 micron support and similar impregnation conditions, changing only the type of supported metal; the metal oxide loadings in all three were similar. Combined with the catalytic results of subsequent application examples, it can be seen that the differences in catalytic performance among different composite catalysts are not primarily due to differences in metal oxide loading, but are closely related to the type of supported metal oxide and its interfacial synergistic effect with the flower-shaped SnO2 micron support. Among them, 1-CoOx / SnO2 exhibited superior activity and target product selectivity in the catalytic oxidation of cyclohexane.

[0073] Application Example 1 50 mg of the 1-CoOx / SnO2 composite catalyst prepared in Example 1 and 17 mL of cyclohexane were added to a 50 mL stainless steel reactor lined with polytetrafluoroethylene. Oxygen was used as the oxidant, and the reaction was carried out under closed conditions. The reaction conditions were set as follows: reaction temperature 130 °C, reaction pressure 1.0 MPa, reaction time 8 h, and magnetic stirring was maintained during the reaction. After the reaction was completed, the reactor was cooled to room temperature, the reaction solution was removed, and the catalyst was removed by centrifugation. The liquid phase products were quantitatively analyzed by gas chromatography (GC) and high-performance liquid chromatography (HPLC).

[0074] Tests showed that under these conditions, the cyclohexane conversion rate was 14.8%, and the total selectivity for cyclohexanone and cyclohexanol was 89.5%.

[0075] Application Example 2 The 4-CuOx / SnO2 composite catalyst prepared in Example 4 was used to carry out the catalytic oxidation of cyclohexane under the same reaction conditions and steps as in Application Example 1. Quantitative analysis of the liquid phase products was performed by gas chromatography (GC) and high-performance liquid chromatography (HPLC). The cyclohexane conversion rate was 10.2%, and the overall selectivity for cyclohexanone and cyclohexanol was 89.3%.

[0076] Application Example 3 The 5-MnOx / SnO2 composite catalyst prepared in Example 5 was used to carry out the catalytic oxidation of cyclohexane under the same reaction conditions and steps as in Application Example 1. Quantitative analysis of the liquid phase products was performed by gas chromatography (GC) and high-performance liquid chromatography (HPLC). The cyclohexane conversion rate was 12.6%, and the total selectivity for cyclohexanone and cyclohexanol was 88.7%.

[0077] Comparative Example 1 This comparative example adopts the technical solution of Example 1. The difference from Example 1 is that in step (1), the addition of citric acid is omitted, and a non-floral SnO2 micron support is obtained; then the non-floral SnO2 micron support is used in step (2). The remaining conditions are the same as in Example 1. This comparative example obtains a non-floral SnO2-based composite catalyst loaded with metal oxide, denoted as N-CoOx / SnO2.

[0078] The N-CoOx / SnO2 composite catalyst prepared in this comparative example was used to carry out the catalytic oxidation of cyclohexane under the same reaction conditions and procedures as in Application Example 1. Quantitative analysis of the liquid phase products was performed by gas chromatography (GC) and high-performance liquid chromatography (HPLC). The cyclohexane conversion rate was 9.7%, and the overall selectivity for cyclohexanone and cyclohexanol was 85.4%.

[0079] Comparative Example 2 This comparative example adopts the technical solution of Example 1. The difference from Example 1 is that in step (1), no annealing treatment is performed, and the flower-shaped SnO2 micron support after vacuum drying is directly used in step (2). The other conditions are the same as in Example 1. The composite catalyst prepared in this comparative example is denoted as NO-CoOx / SnO2.

[0080] The NO-CoOx / SnO2 composite catalyst prepared in this comparative example was used to carry out the catalytic oxidation of cyclohexane under the same reaction conditions and steps as in Application Example 1. Quantitative analysis of the liquid phase products was performed by gas chromatography (GC) and high-performance liquid chromatography (HPLC). The cyclohexane conversion rate was 11.3%, and the total selectivity for cyclohexanone and cyclohexanol was 86.9%.

[0081] Table 2 summarizes the cyclohexane catalytic oxidation performance of the composite catalysts in Application Examples 1-3 and Comparative Examples 1-2: Table 2. Summary of the cyclohexane catalytic oxidation performance of the composite catalysts in Application Examples 1-3 and Comparative Examples 1-2

[0082] Application Example 4 To test the cyclic stability of the flower-like SnO2-based composite catalyst supported on metal oxides of the present invention, the 1-CoOx / SnO2 composite catalyst prepared in Example 1 was used to repeatedly carry out the catalytic oxidation reaction of cyclohexane under the same reaction conditions as in Application Example 1. After each reaction, the catalyst was collected by centrifugation, washed with anhydrous ethanol, dried, and reused in the next reaction. This cycle was repeated three times, and the cyclohexane conversion and the total selectivity of cyclohexanone and cyclohexanol were tested in each cycle. The specific results are shown in Table 3: Table 3 Summary of the cyclic catalytic performance of the composite catalyst in Example 1

[0083] Depend on Figures 1 to 6 It can be seen that the flower-like SnO2 micron-carrier prepared in Example 1 exhibits a relatively regular flower-like micron structure, which is composed of a large number of self-assembled nanosheet units, with obvious hierarchical structure characteristics and a large number of surface exposed sites. Figure 1 After loading with metal oxides, the resulting flower-like SnO2-based composite catalyst still largely maintained its intact flower-like micron morphology, indicating that the loading and calcination processes did not damage the main hierarchical structure of the support; at the same time, its surface became relatively rough, with locally visible particulate deposits, indicating that the surface morphology of the support changed after loading. Figure 2 In contrast, the sample obtained in Comparative Example 1 did not form a regular flower-like microstructure, but mainly exhibited irregular aggregated particles or blocky stacking morphology, with poor structural uniformity and indistinct hierarchical structure characteristics. Figure 3 Furthermore, BET test results further indicate that the specific surface area of ​​the flower-like SnO2 micron-sized carrier in Example 1 is 39.3159 m². 2 / g, significantly higher than the 5.1589m of the non-florescent SnO2 micron-sized support in Comparative Example 1. 2 / g, approximately 7.6 times that of the latter ( Figure 4 and Figure 5 This indicates that the flower-like hierarchical structure can help increase the specific surface area of ​​the support and provide more surface sites for anchoring active components and contacting reactants. Furthermore, according to the XRD results, the main diffraction peaks of the flower-like SnO2 micron support in Example 1 correspond to the SnO2 standard card (JCPDS 41-1445), indicating that the obtained sample has a good degree of crystallization and no obvious impurity phase peaks, suggesting that the prepared support is mainly composed of crystalline SnO2 (…). Figure 6 ).

[0084] In summary, the SEM, BET, and XRD characterization results corroborate each other, indicating that the present invention has successfully constructed a SnO2 micron-sized support with a flower-like hierarchical structure, a large specific surface area, and a well-defined crystal phase structure. Furthermore, this structure can be well preserved during the subsequent metal oxide loading process, which is beneficial to the construction of the composite catalyst interface structure and the improvement of catalytic performance.

[0085] As shown in Tables 2 and 3, the flower-like SnO2 support / metal oxide composite catalytic system constructed in this invention exhibits significant performance advantages in the cyclohexane oxidation reaction. Taking the 1-CoOx / SnO2 catalyst of Example 1 as an example, its cyclohexane conversion rate is 14.8%, and the total selectivity for cyclohexanone and cyclohexanol is 89.5%, which is significantly better than the N-CoOx / SnO2 catalyst prepared using a non-flower-like support (9.7%, 85.4%), and also significantly better than the NO-CoOx / SnO2 catalyst prepared using an unannealed support (11.3%, 86.9%). This indicates that the flower-like hierarchical structure, the introduction of transition metal oxides, and annealing treatment are all beneficial to improving the catalyst activity and the selectivity of the target product. Meanwhile, 4-CuOx / SnO2 and 5-MnOx / SnO2 also exhibited catalytic performance of 10.2% and 89.3%, and 12.6% and 88.7%, respectively, indicating that the flower-like SnO2 support has certain applicability to different transition metal oxides. Among them, 1-CoOx / SnO2 showed a better overall effect in terms of activity and selectivity. Table 3 further shows that after three consecutive cycles, the cyclohexane conversion rate of the 1-CoOx / SnO2 catalyst only decreased from 14.8% to 13.9%, while the total selectivity of cyclohexanone and cyclohexanol remained at approximately 89%, indicating that the composite catalyst can maintain relatively stable catalytic performance during repeated use. In summary, this invention, by constructing a flower-like SnO2 micron support and loading transition metal oxides, not only improves the activity and target product selectivity of the catalyst, but also helps to enhance the structural stability and recycling stability of the catalyst.

[0086] Unless otherwise stated, all percentages used in this invention are mass percentages.

[0087] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a flower-like SnO2-based composite catalyst supported on a metal oxide, characterized in that, Includes the following steps: Step S01: Add sodium hydroxide solution to ethanol aqueous solution, disperse and dissolve, then add tin tetrachloride pentahydrate and citric acid, mix well to obtain precursor solution; after hydrothermal reaction of precursor solution in closed environment, collect solids by centrifugation, wash and dry solids, and then anneal to obtain flower-shaped SnO2 micron support. Step S02: Add the flower-shaped SnO2 micron support to the transition metal nitrate solution for impregnation treatment; after the impregnation treatment is completed, centrifuge to collect the solid, and then calcine the solid after drying to obtain the flower-shaped SnO2-based composite catalyst loaded with metal oxide. The transition metal nitrate used in the transition metal nitrate solution is at least one of the following: cobalt nitrate, copper nitrate, ferric nitrate, manganese nitrate, and zinc nitrate; The total molar concentration of transition metal nitrates in the transition metal nitrate solution is 0.1-1.5 mol / L.

2. The method for preparing the flower-like SnO2-based composite catalyst supported on metal oxides according to claim 1, characterized in that, In step S01, the concentration of the sodium hydroxide solution is 0.8-1.2 mol / L; The volume concentration of ethanol in an aqueous ethanol solution is 40-60%.

3. The method for preparing the flower-like SnO2-based composite catalyst supported on metal oxides according to claim 1, characterized in that, In step S01, the concentration of sodium hydroxide in the precursor solution is 0.3-0.5 mol / L; The molar ratio of sodium hydroxide, tin tetrachloride pentahydrate, and citric acid in the precursor solution is 9-12:1:0.2-0.

5.

4. The method for preparing the flower-like SnO2-based composite catalyst supported on metal oxides according to claim 1, characterized in that, In step S01, the hydrothermal reaction temperature is 150-250℃ and the hydrothermal reaction time is 15-30h.

5. The method for preparing the flower-like SnO2-based composite catalyst supported on metal oxides according to claim 1, characterized in that, In step S01, the annealing process is carried out in an air atmosphere at a temperature of 400-550℃ for 3-7 hours.

6. The method for preparing the flower-like SnO2-based composite catalyst supported on metal oxides according to claim 1, characterized in that, In step S02, the mass-to-volume ratio of the flower-like SnO2 micron support to the transition metal nitrate solution is 0.9-1.2 g: 100 mL.

7. The method for preparing the flower-like SnO2-based composite catalyst supported on metal oxides according to claim 1, characterized in that, In step S02, the immersion treatment temperature is room temperature, and the immersion treatment time is 5-18 hours. The calcination process is carried out in an air atmosphere at a temperature of 400-500℃ for 3-6 hours.

8. A flower-like SnO2-based composite catalyst supported on a metal oxide, characterized in that, It is prepared by the preparation method according to any one of claims 1-7.

9. The application of the flower-like SnO2-based composite catalyst supported on metal oxide as described in claim 8 in the catalytic oxidation of cyclohexane to prepare cyclohexanol and cyclohexanone.

Citation Information

Patent Citations

  • Preparation method of SnO2 / C composite microflowers and obtained product

    CN106757527A

  • Preparation method of SnO2 / CoOOH micron-flower material prepared from graded nano-rods

    CN108726558A

  • Size homogenization method of SnO2 / SnS2 flower-ball-shaped micron-sized particles

    CN114804190A

  • Preparation method and application of gold-loaded tin dioxide catalyst

    CN119701951A

  • Nitrogen plasma vapor deposition modified metal oxide catalyst as well as preparation method and application thereof

    CN120866864A